Subjective perceptions of age-related gains buffer negative associations of perceived age-related losses with health, well-being, and engagement. (March 2022) - Windsor, Tim D.; Abbott, Mandy J.; Cations, Monica; Howard, Alexis J.; Wilton-Harding, Bethany
People reflect on their own aging, and this subjective awareness has an influence on developmental outcomes. Scholars have recently operationalized subjective aging in terms of awareness of age-related change (AARC), which captures awareness of both gains and losses. We examined associations of AARC-gains and AARC-losses with physical functioning, subjective well-being, and engagement with life (enjoyable activities and sense of purpose). Importantly, we extended previous research by not only assessing main effects of gains and losses but also testing their interaction. We hypothesized that awareness of losses would be more weakly negatively associated with health and well-being among those who possessed higher awareness of gains. A total of 399 older participants aged 65 to 91 (235 women and 164 men) were recruited via Prime Panels crowd-sourcing platform to complete an online questionnaire. Greater AARC-losses was associated with poorer health, lower subjective well-being, and lower sense of purpose. AARC-gains was associated with better outcomes in general, and moderated associations of AARC-losses with physical functioning, subjective well-being, and sense of purpose (but not engagement in leisure activities). Consistent with predictions, moderation effects showed that negative associations of AARC-losses with the outcomes were weaker among those who reported higher AARC-gains. Results provided some support for a role of AARC-gains in buffering negative effects of AARC-losses on developmental outcomes.